2024
DOI: 10.3390/microorganisms12010183
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fourier Transform Infrared Spectroscopy to Discriminate Two Closely Related Bacterial Species: Bacillus anthracis and Bacillus cereus Sensu Stricto

Viviana Manzulli,
Miriam Cordovana,
Luigina Serrecchia
et al.

Abstract: Fourier transform infrared spectroscopy (FTIRS) is a diagnostic technique historically used in the microbiological field for the characterization of bacterial strains in relation to the specific composition of their lipid, protein, and polysaccharide components. For each bacterial strain, it is possible to obtain a unique absorption spectrum that represents the fingerprint obtained based on the components of the outer cell membrane. In this study, FTIRS was applied for the first time as an experimental diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The region of the FTIR spectrum that showed the discrimination of B. anthracis/B. cereus isolates was found to be in the region 1300-700 cm −1 , corresponding to the absorption wave numbers of polysaccharides [40]. Once again, the technique is capable of discriminating pathogens of interest to health; in this case, it was applied to humans but can be extrapolated to animals.…”
Section: Infections By Different Classes Of Pathogens Can Be Diagnose...mentioning
confidence: 98%
“…The region of the FTIR spectrum that showed the discrimination of B. anthracis/B. cereus isolates was found to be in the region 1300-700 cm −1 , corresponding to the absorption wave numbers of polysaccharides [40]. Once again, the technique is capable of discriminating pathogens of interest to health; in this case, it was applied to humans but can be extrapolated to animals.…”
Section: Infections By Different Classes Of Pathogens Can Be Diagnose...mentioning
confidence: 98%
“…Several studies have shown that FTIR spectroscopy has high discriminatory power, enabling differentiation at the species or subspecies level [ 10 , 22 , 23 ]. It has been successfully employed for strain typing of pathogens such as Legionella pneumophila , Pseudomonas aeruginosa , Streptococcus pneumoniae , Bacillus cereus group, and Staphylococcus aureus [ 21 , 24 , 25 , 26 , 27 ]. A variety of FTIR-based methodologies have been utilized across microbial studies for tasks beyond microbial identification, such as process monitoring, cell wall analysis, biofilm examination, stress response assessment, and investigation of environmental interactions (reviewed by [ 23 , 28 ]).…”
Section: Introductionmentioning
confidence: 99%